The Potential of Land-Use Change to Mitigate Water Scarcity in Northeast Germany – a Review - Lischeid, Gunnar; Nathkin, Marco (DIE ERDE – Journal of the Geographical Society of Berlin, 2011)
Climate change is expected to increase water scarcity in northeast Germany. Land-use change is one of the options of mitigation that is intensely discussed in this region. This review aims at giving a compilation of existing data and modelling studies in order to investigate the potential and the limits of the land-use change approach.